Penguatan Identitas Budaya Lokal Melalui Pelestarian Kesenian Gambang Kromong pada Sanggar Jali Putra di Jakarta - Hudaepah, Hudaepah (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2025)
Gambang Kromong is a traditional Betawi art combining gamelan elements with Chinese musical instruments. Currently, this art faces a cultural shift, neglected by the younger generation as they favor western music to traditional one. The youth’s efforts highly contribute to the preserved existence of traditional arts, one of which is through the Jali Putra art studio. This study strengthens the local cultural identity and maintains the existence of the Gambang Kromong traditional art. This study aims to contribute to the progress of preserving local cultures and traditional arts. It employed an ethnographic method with a holistic approach. The data were collected by means of direct observation, in-depth interviews, documentation, and literature reviews. The findings showed that strengthening local cultural identity is a pivotal role for art studios as it preserves the cultural heritage for the younger generations. Through cultural education, the youth’s involvement in cultural festival activities appears to be an effective endeavour in preserving the Gambang Kromong traditional arts. Finally, this study expectedly advances the preservation of local culture, especially traditional arts.